2007
DOI: 10.1016/j.ypmed.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Commercial venues as supports for physical activity in adolescent girls

Abstract: Objective-The purposes of this study were to describe the types and availability of commercial facilities for physical activity (PA) in six diverse geographic areas (Washington DC and Maryland; South Carolina; Minnesota; Louisiana; Arizona; and California) and to assess the relationship between those facilities and the non-school PA of adolescent girls.Methods-A total of 1556 6th grade girls participating in the Trial of Activity for Adolescent Girls (TAAG) wore accelerometers for 7 days providing 6 days of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
(32 reference statements)
3
29
1
Order By: Relevance
“…Our finding that objectively measured park availability was not associated with either park use or physical activity is inconsistent with several studies demonstrating positive associations between availability and adolescent physical activity [6,7,[9][10][11][12][13]. There are, however, studies that did not find an association [3,8] or found differences by gender [9,11,13].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding that objectively measured park availability was not associated with either park use or physical activity is inconsistent with several studies demonstrating positive associations between availability and adolescent physical activity [6,7,[9][10][11][12][13]. There are, however, studies that did not find an association [3,8] or found differences by gender [9,11,13].…”
Section: Discussioncontrasting
confidence: 99%
“…Evidence from studies using measures of perceived facility availability is mixed, with some finding positive associations [1][2][3] and others finding no associations [4,5]. The majority of work in this area, however, utilizes objective measures of facility availability and provides strong evidence indicating that a greater availability of recreational facilities is positively associated with adolescents' physical activity levels [3,[6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Findings from the present investigation are consistent with several recent studies [13,35,39,40] that used GIS methods to examine the relationship between PA facilities and adolescents' PA. For example, Gorden-Larsen et al [39] reported that the relative odds of achieving five or more bouts of MVPA per week were increased when adolescents had one or more commercial PA facilities within a 8.07-km buffer around their residence as compared to adolescents with zero facilities. Powell et al [40] reported that number of commercial physical activity-related facilities increased frequent VPA by 9.0% in 12th girls.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, there is a positive significant correlation between perceived facility access and multipurpose PA facilities (Table 4) in the SEM model. In adults [33,34] and sixth grade girls [35], access to objectively measured facilities was significantly related to PA even after controlling for selected personal and social variables.…”
Section: Discussionmentioning
confidence: 89%
“…Studies with adolescents have shown a positive correlation between presence and proximity of such facilities and physical activity levels (Norman et al, 2006;Dowda et al, 2007;Pate et al, 2008;Tucker et al, 2009). …”
Section: Characteristics Of the Social And Built Environment (Neighbomentioning
confidence: 99%